The Ha-ha : Poems - Kirby, David, 1944- (Book collections on Project MUSE., 2003)
A feature of English landscape architecture, a ha-ha is a wall at the bottom of a ditch; its purpose is to allow the presence of cows and sheep on one''s lawn, but at an agreeable distance and with none of the malodorous unsightliness that proximity would bring. Similarly, The Ha-Ha, the latest offering from poet David Kirby, is both an exploration of the ways in which the mind invites chaos yet keeps it at a distance and an apologia for humor, reflecting Irish poet Patrick Kavanagh''s observation that tragedy is merely underdeveloped comedy. Embracing wit, wide-ranging scholarship, and an equ.